Necessity of the inclusion of borders in value of cultivation and use trials in upland rice - Marcelo Eduardo Forni de Mattos; Flávia Barbosa Silva Botelho; Gabriel Mendes Vilella; Douglas Goulart Castro; Bruno Manoel Rezende Melo; Tácio Peres da Silva (Revista Agrogeoambiental, 2019)
Experimental accuracy in crop research is directly affected by the size of plots. For this reason, researchers use empirical knowledge to determine plot size. There are also other important aspects for determining ideal plot size. These include the type of crop and the use, or not, of borders. The objective of this research was to verify the necessity of including border material in the value of cultivation and use trials in breeding programs of upland rice and to evaluate the experimental accuracy with and without the inclusion of borders. The research was conducted in an experimental area at the Federal University of Lavras, located in the State of Minas Gerais, during three harvests (2014/2015, 2015/2016, 2016/2017). Thirteen upland rice strains and methods of evaluation (useful area and border) were evaluated. A randomized complete block design with three replications was used to evaluate grain yield. Individual analyses of variance were performed considering the useful areas and the borders for the three agricultural years. A joint analysis was also performed with the use of a subdivided plot involving the location of the harvest in terms of the useful area and border among the rice strains. It was concluded it is necessary to use borders in the value of cultivation and use trials in breeding programs of upland rice as it contributes to the performance and experimental accuracy of research results.